Study of Female College Graduates Employment in an Age of Gender Equality (International Journal of Innovative Research in Engineering & Management, 2021)
Following ratification of the United  Nations (UN) Convention on the Elimination of All Forms  of Discrimination Against Women, the Japanese  government enacted the Law Respecting the Improvement  of the Welfare of Women Workers, Including the  Guarantee of Equal Opportunity and Treatment Between  Men and Women in Employment (the Equal Opportunity  Act) in 1985 and spent the next twenty-five years  enforcing it. As a result, political obstacles to workplace  gender equality are slowly but gradually disappearing in  Japan. However, in addition to political constraints, social  and structural barriers inside firms also remain. The  elimination of these extra barriers is important if we are to  develop a society where truly egalitarian employment can  be accomplished. It is possible to see some improvements  in these cultural barriers in contemporary Japanese society  as a result of changes in the functions of a college degree  and changes in the family techniques that couples pick  based on their financial situations. Employees' ability to  advance in the workplace today, under the lifetime  employment system, may be a result of their participation  in the competitive promotion process, independent of  gender. College-educated women may still feel significant  hurdles, although they are getting thinner under the  leadership of the national government.
Keywords: Competition; College Graduate; Equality in Workplace; Female Education